2021
DOI: 10.3390/microorganisms9071415
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides and Physical Activity: A Great Hope against COVID 19

Abstract: Antimicrobial peptides (AMPs), α- and β-defensins, possess antiviral properties. These AMPs achieve viral inhibition through different mechanisms of action. For example, they can: (i) bind directly to virions; (ii) bind to and modulate host cell-surface receptors, disrupting intracellular signaling; (iii) function as chemokines to augment and alter adaptive immune responses. Given their antiviral properties and the fact that the development of an effective coronavirus disease 2019 (COVID-19) treatment is an ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 147 publications
(243 reference statements)
0
17
0
Order By: Relevance
“…Antimicrobial peptides (AMPs) are expressed by most living organisms and play important roles in defending against bacterial, viral and fungal infections [16][17][18], as well as adaptive immunity during the development of cancers and autoimmune diseases [19,20]. AMPs with diverse modes of action distinct from conventional antibiotics exhibit potential capacity against infection of MDR bacteria and other pathogens [21,22]. With the advance of nanotechnology, AMP-derived nanomedicines can be designed to treat bacterial infection locally [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) are expressed by most living organisms and play important roles in defending against bacterial, viral and fungal infections [16][17][18], as well as adaptive immunity during the development of cancers and autoimmune diseases [19,20]. AMPs with diverse modes of action distinct from conventional antibiotics exhibit potential capacity against infection of MDR bacteria and other pathogens [21,22]. With the advance of nanotechnology, AMP-derived nanomedicines can be designed to treat bacterial infection locally [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of COVID-19, increased levels of inflammatory cytokines and excessive activation of immune cells called “cytokine storms” have been observed [ 1 , 2 , 3 ]; in particular, cytokine levels were used to assess disease severity, survival, and response to treatment [ 4 , 5 ]. At the same time, antimicrobial peptides (AMPs) are known to be valuable weapons in the body’s defense response against COVID-19 attack [ 6 ]. In humans, the most characterized classes of AMPs are the defensins (α- and β-defensins) [ 7 , 8 ], which are among the main players in the innate immunity system, and are involved in the first line of defense, playing a crucial role in infections and inflammations against pathogenic agents (bacteria, viruses, fungi and parasites) [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These antiviral peptides can work through different mechanisms, ranging from immune regulation to direct inactivation via membrane disruption [ 17 , 18 , 19 , 20 ]. Hence, natural AMPs may be engineered into new therapeutics to help control these viruses [ 11 , 12 , 21 , 22 , 23 ]. As a proof of concept, we previously demonstrated that LL-37 could be engineered to inhibit Ebola virus entry [ 24 ].…”
Section: Introductionmentioning
confidence: 99%